Die Übersetzungen der Elementatio Theologica des Proklos und ihre Bedeutung für den Proklostext - Günther, Hans Christian. (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2007)
The present book presents for the first time a detailed study of selected passages of the most important Georgian translation of a text of Greek philosophy: the translation of Proklos' Elementatio Theologica by the most eminent philosopher of the Georgian middle ages, Ioane Petrizi, who not only translated Proklos' text, but also provided it with an extensive commentary. The book discusses the paragraphs which are also extant in an Arabic translation of the early 9th century. The main scope of the book is to establish the relevance of the Georgian and Arabic translations for the history of the constitution of the text, but it provides also important insights in Petrizi's method of translation and the philosophical significance of his commentary.